Sub-Saharan African Cotton Policies in Retrospect - (:unkn) unknown (My University, 2011)
Calls for liberalizing cash crop sectors in sub-saharan Africa have been voiced for decades. Yet, the impact of reforms remains elusive in empirical studies. This paper offers new opportunities to solve this problem by creating precise and consistent market organisation indices for 25 African cotton markets from 1961 to 2008. The aggregation of scores reveals interesting trends : markets are not more competitive today than in the late 1990s, 50% of production still originates from markets with fixed prices and reforms are giving rise to a new type of regulated markets with mixed ownership both in East and West Africa.
Keywords: African Research